(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2026)
This article highlights the modern pedagogical foundations for improving the professional training of future physical education teachers. The study analyzes practice-oriented mechanisms for developing professional competence in the context of educational transformation, as well as the potential of innovative pedagogical technologies and the digital educational environment. In addition, the content of the modified SPORTER didactic concept based on a learner-centered approach is revealed, and its significance in shaping future physical education teachers as reflective, innovative, and professionally autonomous subjects is substantiated.